Blogging in the Classroom: Technology, Feminist Pedagogy, and Participatory Learning - Roth, Jenny (Atlantis, 2008)
This exploration of blogs as a tool for enhancing feminist participatory learning is situated within extant technofeminist debates and grows out of assignments in a feminist cultural studies class. The paper considers how blogs generally support all aims of participatory learning, connectivity and identity politics in particular.